2018
DOI: 10.3389/fneur.2018.00696
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Cord Changes After Laminoplasty in Cervical Compressive Myelopathy: A Diffusion Tensor Imaging Study

Abstract: Purpose: Validation of the efficacy of decompression surgery in patients with cervical myelopathy (CM) is important in terms of the recovery of the integrity of the spinal cord. However, to date, no longitudinal study has addressed the underlying pathological changes using diffusion tensor imaging (DTI) in CM patients. This study aimed to determine the diffusion metrics at the lesion as well as below the lesion level longitudinally in CM patients following laminoplasty using DTI.Methods: Twenty CM patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…DTI effectiveness in predicting prognosis of CSM patients has been widely investigated and accepted (7 studies level of evidence II, 1 study level of evidence III). 20,[40][41][42][43][44][45] Furthermore, Rao and Severino's findings were concordant in identifying transfer area (TA) values of 0.55 as a cutoff for the prognosis of CSM patients. Rao et al 45 found preoperative TA < 0.55 to be associated with significantly poorer outcome (class II evidence).…”
Section: Group 7: Follow-up and Outcomementioning
confidence: 82%
See 1 more Smart Citation
“…DTI effectiveness in predicting prognosis of CSM patients has been widely investigated and accepted (7 studies level of evidence II, 1 study level of evidence III). 20,[40][41][42][43][44][45] Furthermore, Rao and Severino's findings were concordant in identifying transfer area (TA) values of 0.55 as a cutoff for the prognosis of CSM patients. Rao et al 45 found preoperative TA < 0.55 to be associated with significantly poorer outcome (class II evidence).…”
Section: Group 7: Follow-up and Outcomementioning
confidence: 82%
“…In a prospective multicenter study, Ozawa et al [ 39 ] observed that preoperative intramedullary Gd-DTPA enhancement was indicative of poor prognosis. DTI effectiveness in predicting prognosis of CSM patients has been widely investigated and accepted (7 studies level of evidence II, 1 study level of evidence III) [ 20 , 40 - 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Successful spinal cord tractography depends on many factors, such as image acquisition settings, region of interest design, and distortion correction [ 19 , 20 ]. With the development of imaging techniques and the availability of excellent software, it is now possible to discriminate between detailed structures, such as columns within the spinal cord, which enables tract-specific analysis [ 15 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%